A COMPREHENSIVE SYSTEMATIC REVIEW OF THE ASSOCIATION BETWEEN THALASSAEMIA MAJOR, ENDOCRINE COMPLICATIONS AND QUALITY OF LIFE - Jeffy Marta (International Medical Journal Corp. Ltd, 2026)
Introduction: Thalassaemia major (TM) is the most severe transfusion-dependent form of β-globin chain synthesis failure, transformed from a fatal paediatric disease into a chronic multisystem disorder of adulthood. The price of survival gain is cumulative transfusional iron overload targeting the anterior pituitary, pancreatic islets, thyroid, parathyroids, gonads and skeleton. Endocrine complications constitute the dominant morbidity of adult TM, intersecting directly with health-related quality of life (HRQoL). This review quantified endocrine morbidity in TM and its relationship to HRQoL. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligible designs comprised randomised controlled trials, cohort, case-control, cross-sectional and observational studies. Systematic reviews were excluded from primary tabulation but retained for corroboration. Two reviewers independently screened, extracted data and appraised risk of bias using Newcastle-Ottawa Scale, JBI checklist and RoB 2; certainty was graded with GRADE. Sixteen prespecified outcomes were synthesised narratively with structured tabulation. Results: Forty-seven primary studies encompassing >10,000 patients across 20 countries met eligibility. Multiple endocrinopathy affected 56% of TM patients versus 13% of transfused sickle-cell controls (p<0.001), adjusted odds ratio 9.4 (p<0.001). Hypogonadism was most frequent (40-56.7%), followed by growth failure (24-50.5%), glucose disorders (6.4-34%), thyroid dysfunction (6.5-19.9%), hypoparathyroidism (2.2-12.8%) and osteoporosis (21.6-89%). In a population-based English cohort, 76% had ≥1 comorbidity, 54% ≥2 and 37% ≥3; 10-year mortality 6.2% versus 1.2% in general population (p<0.001). Ferritin ≥1000 ng/mL predicted heart failure (HR 3.35) and death (HR 2.45). Pancreatic T2* <13.07 ms predicted abnormal glucose tolerance; normal pancreatic T2* carried 100% negative predictive value for dysglycaemia. HRQoL was significantly impaired relative to population norms: five of eight SF-36 subscales and both component summaries reduced (p<0.05); EQ-VAS 67.1 versus 80.4, FACT-G 70.1 versus 77.0, FACIT-Fatigue 27.9 versus 43.6 (all p<0.001). Female sex, older age, higher ferritin and greater complication number were independent determinants of poorer HRQoL. Gene editing exceeded minimal clinically important difference thresholds across all instruments; luspatercept responders achieved clinically meaningful SF-36 physical component improvement more often than placebo (31.1% vs 16.5%, p=0.024). GRADE certainty was moderate for six outcomes, low for eight, very low for two. Discussion: The evidence describes a coherent chain: transfusional iron loading produces organ-specific siderosis; endocrinopathies accumulate with age and iron exposure; this burden independently impairs HRQoL. Critically, the relationship is modifiable. Intensive chelation normalised glucose metabolism in 44%, permitted thyroxine discontinuation in 10/18 and testosterone in 7/14, while long-term deferasirox significantly improved lumbar bone mineral density (p<0.001) and reduced osteoporosis (p=0.022). Contemporary optimally managed cohorts show attenuated endocrine phenotype, whereas resource-constrained cohorts show the opposite. The dominant determinant is therefore not genotype but adequacy of iron control. Conclusion: Thalassaemia major is associated with high, statistically significant, multi-axis endocrine complication burden that accumulates with age and iron exposure and translates into significant HRQoL impairment across physical, psychological and social domains. Because the relationship between iron burden, endocrinopathy and quality of life is modifiable, structured age-stratified endocrine surveillance, aggressive organ-specific iron control guided by magnetic resonance relaxometry rather than ferritin alone, and routine longitudinal patient-reported outcome measurement should be core, non-optional components of comprehensive thalassaemia care.